Effectivity Combination of Bitter Melon (Momordica charantia) and Bitter (Andrographis paniculata) Extract to Suppress Proinflammatory Cytokines in Diabetic Mouse Models - Agustin, Firda (Biotropika: Journal of Tropical Biology, 2015)
nsulin Resistance (IR) is main characteristic of Type 2 Diabetes Mellitus. IL-6 and IFNÎ³ play important role in the deterioration of this disease. The aim of this experiment was to know effectivity combination of Bitter Melon and Bitter to decrease the expression of IL-6 and IFNÎ³ in Type 2 Diabetes Mellitus. Type 2 Diabetes Mellitus were induced by injecting streptozotocin to neonate BALB/c mice in the age of five days (100 mg/kg BW). This experiment applied five groups which divided into Â normal group, T2D (Type 2 Diabetes Mellitus model group), T2D-D1 (Bitter Melon dose 5,6 mg/kg BW and Bitter 20 g/kg BW), T2D-D2 (Bitter Melon doses 56 mg/kg BW and Bitter doses 200 mg/kg BW) and T2D-D3 (Bitter Melon doses 5600 mg/kg BW and Bitter doses 20000 mg/kg BW). Relative number of proinflammatory cytokines were analyzed using One-Way ANOVA with SPSS 16.0 for Windows. The results showed that the treatment with Bitter melon (Momordica charantia) and bitter (Andrographis paniculata) gave different effect compared to T2D groups. Medicinal herbs groups supressed proinflamatory cytokines such as IL-6 and IFNÎ³. So that relative number of IL-6 and IFNÎ³ in treated group is lower than Type 2 Diabetes Mellitus (T2D) mice model. Â  Key words: IFNÎ³, IL-6, Insulin, Proinflammatory